2013
DOI: 10.1073/pnas.1221217110
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of prosocial behavior across diverse societies

Abstract: Humans are an exceptionally cooperative species, but there is substantial variation in the extent of cooperation across societies. Understanding the sources of this variability may provide insights about the forces that sustain cooperation. We examined the ontogeny of prosocial behavior by studying 326 children 3-14 y of age and 120 adults from six societies (age distributions varied across societies). These six societies span a wide range of extant human variation in culture, geography, and subsistence strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
257
3
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 371 publications
(301 citation statements)
references
References 44 publications
(38 reference statements)
19
257
3
8
Order By: Relevance
“…We conducted our experiment with girls and boys of ages five and eight to evaluate exactly this kind of possibility. More to the point, existing behavioral evidence suggests that prosocial behavior varies for children of ages five and eight, and the degree of prosocial behavior could also be different for boys and girls (Benenson et al, 2007;Fehr et al, 2008;Blake and McAuliffe, 2011;House et al, 2013). If this is true, insofar as all prosocial behavior depends on payoff-irrelevant social cues, children in different age-sex categories should respond differently to these cues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted our experiment with girls and boys of ages five and eight to evaluate exactly this kind of possibility. More to the point, existing behavioral evidence suggests that prosocial behavior varies for children of ages five and eight, and the degree of prosocial behavior could also be different for boys and girls (Benenson et al, 2007;Fehr et al, 2008;Blake and McAuliffe, 2011;House et al, 2013). If this is true, insofar as all prosocial behavior depends on payoff-irrelevant social cues, children in different age-sex categories should respond differently to these cues.…”
Section: Resultsmentioning
confidence: 99%
“…Children represent an informative subject pool because previous research has shown that young children, like adults, care about their reputations (Engelmann et al, 2012(Engelmann et al, , 2013, and thus they have a reputational psychology that can be experimentally manipulated. Moreover, past research also suggests that altruistic behavior changes between the ages of five and eight, and this developmental process is potentially different for girls and boys (Benenson et al, 2007;Fehr et al, 2008;Blake and McAuliffe, 2011;House et al, 2013). For these reasons, children provide a potential means of addressing both the weak and strong hypotheses.…”
Section: Introductionmentioning
confidence: 99%
“…This difference appears early in ontogenesis-for instance, 10-month-old toddlers prefer faces of their race (Kinzler and Spelke, 2011). Presumably, attitudes toward in-and out-group members are formed via moral rules that emerged during phylogeny and can be fixed in genes and culture (House et al, 2013). The preference for unrelated group members may therefore be formed within culture early in ontogenesis but later than the preference for related group members.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas several studies found that different countries exhibit cooperation rates of varying magnitude (27)(28)(29)(30)(31), specific empirical evidence on cross-societal cooperation with interaction partners from different nations is still scarce and limited to the comparison between few countries involving mainly student populations. However, these studies provide noteworthy first evidence that expectations and the willingness to cooperate vary with the nationality of the interaction partner (32,33).…”
Section: Significancementioning
confidence: 99%